Manfaat Kredit Usaha Rakyat Bagi Pelaku Usaha Kecil Dan Menengah Di Kecamatan Langke Rembong Kabupaten Manggarai : Studi Pada BRI Cabang Ruteng - Viktoria Wulandari; Novi Theresia Kiak; Cicilia Apriliana Tungga (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to explain the benefits of providing BRI Bank People's Business Credit loans for Small and Medium Enterprises. This research was conducted at Bank Rakyat Indonesia because it is one of the banks that distributes the KUR assistance program. This research uses primary data and secondary data. The research results show the benefits of providing BRI bank KUR assistance to SMEs, namely that small and medium business actors are helped by getting capital to open a business, develop businesses that are already running and can provide employment assistance for other people. Obstacles that small and medium business actors often face when applying for small and medium business credit assistance include incomplete requirements, bad personalities and inappropriate credit guarantees. It is hoped that the provision of people's business credit loans will be able to provide benefits to small and medium business owners, both for the businesses they run and to fulfill other economic needs.